Jejak Ekologi Sebagai Pendekatan Integratif Sustainable Development Goals (Sdgs) dan Green Economy di Indonesia - Inud Danis Ikhwan Meranti; Zainal Aris Masruchi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Sustainable Development Goals (SDGs) set a set of goals to end poverty, protect the planet, and ensure a peaceful and prosperous life for all. One of the important aspects in the integration of the SDGs with the concept of Green Economy is the role of ecological footprints. Ecological footprint refers to the impact of human activities on the environment, including the consumption of natural resources and waste production. In the context of the Green Economy, ecological footprint is an important indicator to measure the efficiency of natural resource use and the environmental impact of economic activities. This research uses relevant literature analysis and synthesis methods from various sources such as scientific journals, books, research reports, and policy documents. The Sustainable Development Goals (SDGs) with the concept of Green Economy, which is applied with an ecological footprint approach, are an integral strategy to achieve sustainable and environmentally friendly economic growth.